Religion and Politics in Swaziland - Kumalo, Simangaliso (UJ Press, 2013)
The author offers a candid reflection on the interface between politics and religion in Swaziland by reflecting on the works of Joshua Mzizi. The strength of the book lies in the fact that the author, a public theologian, gives insight into the bigger story - the interface between politics and religion in Africa.